(untitled) (Horizontes de Enfermería, 2018)
In this paper the relationship between levels of pre-competitive anxiety with emotional self-control was analyzed in football referees of the Association of Pichincha. Th e research methodology is not experimental and correlational quantitative transversal character. Since the measurement was performed in a single moment. We worked with a population of 20 professional soccer referees Pichincha. Test HAMILTON anxiety scale (HAS) was applied to the 20 referees. Th e results showed that 15% of them have a very high anxiety prior to the football game level; 85% reveal that they feel a high level in the precompetitive anxiety. Th e questionnaire to measure self-control of football referees endorsed by World Association of Universities for scientifi c studies about football (AMUECFUT) Murguia, G. (2006), the results showed the following information: 40% of the referees show a high level of high control, 60% indicated having an average level of self-restraint in the conduct of a football game. Th e data from the research show that there is relationship between precompetitive anxiety and emotional self-control. A greater precompetitive anxiety less self control football matches and less precompetitive anxiety greater emotional self-control decision-making in the various football matches.